Populærmusikforskning i Danmark: Musikstudier mellem musiksociologi, -analyse og -antropologi: Special section: 70th anniversary of the Danish Musicological Society - Michelsen, Morten (Danish Yearbook of Musicology, 2024)
In this article I document and analyse the field of popular music research in Denmark as an epistemic culture (Knorr Cetina) from its early stages in the 1970s to the present day. I begin with a discussion of how 1960s’ Danish intellectual culture in some ways paved the way for an academic interest in popular music and point towards the first international research initiatives. Then, I analyse the gradual institutionalisation of the field by focussing on publications, hirings, grants, and local and international relations. Finally, I look at changes in what it meant to know about popular music based on Marxist and, later, semiotic and poststructuralist paradigms that popular music research has drawn upon in its efforts to understand still more complex musical cultures. The narrative is structured in three periods: the 1970s and 1980s, the 1990s and 2000s, and the 2010s to 2024. They correspond roughly to the three paradigms mentioned. Basically, the Danish developments have been and are part of an international popular music research field dominated by the UK and the US. Locally employed researchers have contributed to international debates, but dealing with music cultures and practices in local and national contexts is mainly what makes Danish research exceptional. Especially since the mid-1990s the Danish field has prospered by receiving grants for networks and research projects, by filling tenured positions, by developing formal and informal, national and international networks, and by promoting PhD students. At the same time, popular music research has become a fully legitimate object of study – to the extent that a majority of musicologists in Denmark work mainly with popular music. Thus, the field has been a success both qualitatively and quantitatively. At the end, I argue that the distinction between musicology and popular music studies no longer seems relevant, and I recommend that we in the future practice music studies.